Exploring the relationship between athletic and religious identities - Proios, Miltiadis (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The identity theory supports the existence of multiple identities and the fact that they are interrelated. Aim of Study. The present study is an effort to examine this existence in relation to athletic and religious identities as well as whether religious identity plays an important role in predicting the dimensions of athletic identity. Material and Method. The study included 258 athletes (180 males, and 78 females). Their age ranged from 18 to 27 years. Participants filled out the instruments of Athletic Identity Measurement Scale and Santa Clara Strength of Religious Faith Questionnaire. Results. Results revealed the existence of a relation between the two identities as well as the ability of religious identity to predict the dimensions of athletic and social identities. Finally results showed the nonexistence of relation to gender in both identities. Conclusions. In conclusion, the religious beliefs may have an impact on the athletic identity of religious people within the frame of sports. Itis also concluded that the two identities (athletic and religious) include meanings with common characteristics (social)
Keywords: sport; athletic identity; religious identity; relationship